The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.11613/bm.2022.030501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of laboratory biomarkers in liver fibrosis

Abstract: Hepatic cirrhosis is a major health problem across the world, causing high morbidity and mortality. This disease has many etiologies, yet the result of chronic hepatic injury is hepatic fibrosis causing cirrhosis and hepatocellular carcinoma, as the liver’s architecture is progressively destroyed. While liver biopsy is currently the gold standard for fibrosis staging, it has significant disadvantages, leading to a growing interest in non-invasive markers. Direct biomarkers – hyaluronic acid, laminin, collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“… 13 The direct biomarker that can usually be used to diagnose hepatic fibrosis is the ECM secretory protein, the level of which can vary with the degree of hepatic fibrosis. 7 In this study, the serum concentrations of PIIINP, CIV, LN, and HA were significantly higher in the cirrhotic group compared to the hepatic fibrosis group, and the change in concentration can effectively distinguish between hepatic fibrosis and cirrhosis. These four indicators are used as direct serum markers for the assessment and diagnosis of liver fibrosis, and they respond to the dynamic onset and development of liver fibrosis, suggesting damage to the hepatocyte matrix for degradation and clearance.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“… 13 The direct biomarker that can usually be used to diagnose hepatic fibrosis is the ECM secretory protein, the level of which can vary with the degree of hepatic fibrosis. 7 In this study, the serum concentrations of PIIINP, CIV, LN, and HA were significantly higher in the cirrhotic group compared to the hepatic fibrosis group, and the change in concentration can effectively distinguish between hepatic fibrosis and cirrhosis. These four indicators are used as direct serum markers for the assessment and diagnosis of liver fibrosis, and they respond to the dynamic onset and development of liver fibrosis, suggesting damage to the hepatocyte matrix for degradation and clearance.…”
Section: Discussionmentioning
confidence: 55%
“… 5 , 6 Collagen type III N-peptide (PIIINP), type IV collagen (CIV), Laminin (LN), and Hyaluronic acid (HA) have been used as direct serum markers for the diagnosis of liver fibrosis and cirrhosis. 7 Studies have analyzed the normal reference intervals of PIIIP N-P in Northern European children and adults. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean diet is still proposed by international guidelines as the treatment of choice ( 85 , 86 ). To successfully alleviate MAFLD and associated comorbidities, new molecular markers should be identified and use as specific targets for the treatment of this pathology with high cardio-metabolic risk ( 87 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these biomarkers are not organ-specific for the liver, it has been confirmed that in patients with chronic liver diseases and fibrosis, increased production and impaired elimination of HA as well as architectural changes in the liver parenchyma leading to an increase in LN concentration are observed. Serum levels of HA and LN are correlated to the stage of hepatic fibrosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%